ADVANCE DIRECTIVES IN TURKEY'S CULTURAL CONTEXT: EXAMINING THE POTENTIAL BENEFITS FOR THE IMPLEMENTATION OF PATIENT RIGHTS - SERT, GÜRKAN (WILEY-BLACKWELL PUBLISHING, INC, 2010)
Advance directives are not a part of the healthcare service in Turkey. This may be related with the fact that paternalism is common among the healthcare professionals in the country, and patients are not yet integrated in the decision-making process adequately. However, starting from the enactment of the Regulation of Patient Rights in 1998, this situation started to change. While the paternalist tradition still appears to be strong in Turkey, the Ministry of Health has been taking concrete measures in the recent years to ensure that patient rights are implemented in healthcare practice. Therefore, Turkey now seems to be in a transitional period where a move towards a more patient-autonomy centred approach is being supported by the regulatory authorities, as well as the academic circles and the public at large. In the light of this background, this paper aims to examine the potential benefits of advance directives, particularly with regard to their possible effect in the clinical decision-making process of Turkey's context. It will be argued that advance directives, if correctly understood and implemented in the right settings, may be beneficial, particularly for improving communication between patients and healthcare professionals and for implementing of the right to refuse treatment.
Keywords: advance directives; paternalism; patient autonomy; patient right; the right to refuse treatment; PHYSICIANS; CANCER